The Principle of Reliability of Business Trading in the Context of Personal Changes in Partnerships - Garnowski, Konrad (Review of European and Comparative Law, 2022)
The article presents the issue of personal changes in partnerships from the perspective of dangers to the interests of partners of such partnerships and third parties. The analysis is carried out primarily in the context of the norms concerning the national court register, but also the relevant regulations of the Code of Civil Procedure. On this basis, the author evaluates the current regulations and concludes that they pose significant dangers to both partners of partnerships and creditors as third parties. These dangers arise mainly from the way the system of presumptions provided for in the provisions of the Act on the National Court Register is shaped. The author refers to the de lege ferenda postulates expressed in the past and selects the optimal solution from the perspective of implementation of the principle of reliability of business trading, and also presents his own de lege ferenda proposals. In the author’s opinion, in order to secure the interests of a partner withdrawing from a partnership against the risk of attempts to hold him/ her liable for obligations arising after his/her membership in the partnership has ceased, it would be sufficient to grant such a person the right to file an application to remove him/her from the register of entrepreneurs as a partner of the partnership. On the other hand, in order to safeguard the interests of third parties, it would be advisable to broaden the scope of application of the norm arising from Article 14 of the Act on the National Court Register and subject the former partner of a partnership to the rigors of this regulation. In addition, in order to ensure greater transparency of the data disclosed in the register, in the author’s opinion, it is advisable to consider the possibility of introducing, within the framework of the register of entrepreneurs, an institution similar to that provided for on the grounds of land and mortgage register proceedings, concerning the obligation of the court to disclose ex officio an identified inconsistency of the actual state of affairs with the state of affairs disclosed in the register of entrepreneurs.